Determinants of Climate Change Adaptation Strategies in Bundelkhand Region, India - JATAV, SURENDRA SINGH; Singh, Naveen Prakash (Indian Journal of Extension Education, 2023)
The study attempted  examining climate change adaptation strategies in the most backward regions of India, i.e., the Bundelkhand region. Data were collected from 200 farmers during April and May of 2017, and a binary logistic regression model was used to analyze the data. The farmers were most likely to improve irrigation facilities if they have access to institutional credit, information about the weather, and have taken crop insurance. Also, farmers perceived that an increase in temperature, a decline in rainfall, and a decline in water tables motivate and influence farmers to change their cropping pattern from wheat (a water-intensive crop) to chickpea (a less water-intensive crop) to cope with the changing climate. Hence, the present study recommends that since water table is declining continuously and creating water crisis even in the rainy season for agriculture and domestic consumption, community participation in the conservation of water-bodies is vital. Further, the adoption of crop varieties that require less water, are drought tolerant and mature early will help increase farm productivity and reduce cultivation costs. Lastly, an advance regional weather forecasting system capable of providing farmers with accurate information that will enable them to change cropping patterns and adjust farming practices are required.